2021
DOI: 10.3390/s21217083
|View full text |Cite
|
Sign up to set email alerts
|

Deceptive Online Content Detection Using Only Message Characteristics and a Machine Learning Trained Expert System

Abstract: This paper considers the use of a post metadata-based approach to identifying intentionally deceptive online content. It presents the use of an inherently explainable artificial intelligence technique, which utilizes machine learning to train an expert system, for this purpose. It considers the role of three factors (textual context, speaker background, and emotion) in fake news detection analysis and evaluates the efficacy of using key factors, but not the inherently subjective processing of post text itself,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Sentiment analysis (SA) is one of the sections that belong to the NLP field [ 11 ] and is responsible for designing and applying models, techniques, and approaches to identify whether a text deals with objective or subjective information [ 55 ] and, in the last case, to identify whether that information was expressed in a negative, neutral, or positive manner [ 56 ] as well as whether it is strong or weak [ 26 ]. The SA method is used in many fields, especially in social media [ 57 ], such as classifying users’ opinions on social media posts [ 58 , 59 ], or knowing the tendencies of the masses in elections and predicting the final results, in addition to controlling public opinion by understanding the public’s attitudes by analyzing users’ opinions about certain situations [ 32 ].…”
Section: Background Of Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Sentiment analysis (SA) is one of the sections that belong to the NLP field [ 11 ] and is responsible for designing and applying models, techniques, and approaches to identify whether a text deals with objective or subjective information [ 55 ] and, in the last case, to identify whether that information was expressed in a negative, neutral, or positive manner [ 56 ] as well as whether it is strong or weak [ 26 ]. The SA method is used in many fields, especially in social media [ 57 ], such as classifying users’ opinions on social media posts [ 58 , 59 ], or knowing the tendencies of the masses in elections and predicting the final results, in addition to controlling public opinion by understanding the public’s attitudes by analyzing users’ opinions about certain situations [ 32 ].…”
Section: Background Of Studymentioning
confidence: 99%
“…Another study has indicated that many people have difficulty distinguishing between fake news and real news, irrespective of their gender, age, or educational attainment [ 10 ]. Social media platforms have presented a virtual environment for posting [ 11 ], discussion, exchange of views, and global interaction among users [ 12 ], without restrictions on location, time, or content volume [ 13 ]. A survey conducted in 2017 claimed that 67% of people in the US got their news mainly from social media [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In [51], the system introduced in [20] was evaluated to assess its efficacy for identifying intentionally deceptive online content. Three factors (the textual context, the speaker's background, and emotion) were used to attempt to detect deceptive content.…”
Section: Textual Statement Characterizationmentioning
confidence: 99%
“…Several techniques have been proposed to enhance the system, including techniques designed to reduce error [ 41 ], change the way training is performed [ 42 ], and automate network development [ 43 ]. Its use has also been previously demonstrated for a limited number of applications (see, e.g., [ 44 ]).…”
Section: Introductionmentioning
confidence: 99%